The BMPR2, ALK1 and ENG Genes Mutation in Congenital Heart DiseaseAssociated Pulmonary Artery Hypertension - Anggoro Budi Hartopo; Dyah Wulan Anggrahini; Noriaki Emoto; Lucia Kris Dinarti (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2019)
The gene mutation is one of the background underlie the pathogenesis of pulmonary artery hypertension (PAH). Several genes have been recognized to be responsible for the development of PAH. The mutation in transforming growth factor-β (TGF-β) pathway is considered to be major genotype background in heritable PAH. The genetic mutation in bone morphogenetic protein receptor-2 (BMPR2), activin receptor-like kinase 1 (ALK-1) and endoglin (ENG) are known to cause heritable PAH. In congenital heart disease–associated PAH (CHDAPAH), their mutation are also presence.